An ex vivo model to quantitatively analyze cell migration in tissue. Issue 1 (18th September 2017) - O'Leary, Conor J.; Weston, Mikail; McDermott, Kieran W.
Abstract : Background: Within the developing central nervous system, the ability of cells to migrate throughout the tissue parenchyma to reach their target destination and undergo terminal differentiation is vital to normal central nervous system (CNS) development. To develop novel therapies to treat the injured CNS, it is essential that the migratory behavior of cell populations is understood. Many studies have examined the ability of individual neurons to migrate through the developing CNS, describing specific modes of migration including locomotion and somal translocation. Few studies have investigated the mass migration of large populations of neural progenitors, particularly in the developing the spinal cord. Here, we describe a method to robustly analyze large numbers of migrating cells using a co‐culture assay.Results: The ex vivo tissue model promotes the survival and differentiation of co‐cultured progenitor cells. Using this assay, we demonstrate that migrating neuroepithelial progenitor cells display region specific migration patterns within the dorsal and ventral spinal cord at defined developmental time points.Conclusions: The technique described here is a viable ex vivo model to quantitatively analyze cell migration and differentiation. We demonstrate the ability to detect changes in cell migration within distinct tissue region across tissue samples using the technique described here. Developmental Dynamics 247:201–211, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Ex Vivo model of cell migration; quantitative analysis of cell migration; regional specific analysis of tissue samples.